2002
DOI: 10.1182/blood.v99.7.2387
|View full text |Cite
|
Sign up to set email alerts
|

Early hematopoietic reconstitution after clinical stem cell transplantation: evidence for stochastic stem cell behavior and limited acceleration in telomere loss

Abstract: Our inability to purify hematopoietic stem cells (HSCs) precludes direct study of many aspects of their behavior in the clinical hematopoietic stem cell transplantation (HSCT) setting. We indirectly assessed stem/progenitor cell behavior in the first year after HSCT by examining changes in neutrophil telomere length, X-inactivation ratios, and cycling of marrow progenitors in 25 fully engrafted allogeneic HSCT recipients. Donors were sampled once and recipients at engraftment and 2 to 6 months and 12 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…These findings clearly indicate that regulation of telomerase activity and telomere length in the HSC compartment is of critical importance for long-term maintenance of hematopoiesis. Further support for this notion comes from the observations of multiple groups that some degree of telomere shortening occurs in multiple lineages of the blood following human HSC transplantation [19][20][21][22]. Of note, such telomere shortening is most noticeable in the first year post transplant [20].…”
Section: Cd38mentioning
confidence: 67%
“…These findings clearly indicate that regulation of telomerase activity and telomere length in the HSC compartment is of critical importance for long-term maintenance of hematopoiesis. Further support for this notion comes from the observations of multiple groups that some degree of telomere shortening occurs in multiple lineages of the blood following human HSC transplantation [19][20][21][22]. Of note, such telomere shortening is most noticeable in the first year post transplant [20].…”
Section: Cd38mentioning
confidence: 67%
“…19,29 Both observations, the loss of earlier and the gain of more committed CD34 subtypes are in line with other reports. Selleri et al 37 found an eightfold decrease of long-term culture initiating cells in the BM of patients as compared with donors, and Thornley et al 30 described a higher telomere loss in the BM of patients with full donor chimerism. Woolthuis et al 38 reported a loss of quiescence and impaired function of CD34 + /CD38 low cells 1 year after autologous stem cell reinfusion.…”
Section: Discussionmentioning
confidence: 99%
“…10 A differential mobilization is also supported by the observation that mobilized PBSC are not or hardly in G2S phase, 28,29 which is in contrast to BMd CD34 + cells and, particularly, to BM1y cells. 30 In 1997, Anderlini & Körbling assumed a more primitive phenotype of CD34 + cells contained in PBSC compared with BM. 25 Furthermore, they postulated a faster engraftment after PBSC transplantation compared with BM allografting as described before.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, despite telomerase up-regulation, telomere shortening is not fully prevented, [10][11][12][13][14] and may lead to loss of proliferative ability in hematopoietic cells. 5 This is supported by the observation that telomere shortening is increased in the following situations: (1) at times of highest proliferative demand in physiological conditions, such as during expansion of the hematopoietic system during fetal life 15 and in the first years of life; [16][17][18] (2) in children with genetic diseases that combine accelerated telomere shortening of hematopoietic cells and clinical hematopoietic failure, such as dyskeratosis congenita, 19 idiopathic aplastic anemia, 20 Fanconi anemia 21 and ataxia-telangiectasia; 22 (3) with hematopoietic reconstitution after therapeutic administration of cytotoxic agents (bone marrow transplantation, [23][24][25][26][27][28][29][30] chemotherapy administration. 31 In this latter setting, the reported rate of shortening has varied in the different studies; in the transplant setting, telomere shortening has been shown to take place mainly in the first year posttransplant.…”
Section: Introductionmentioning
confidence: 99%